New York State's landmark policies on oversight and compensation for egg donation to stem cell research - Roxland, Beth E (Regenerative medicine, 2012)
In 2009, New York became the first US state to implement a policy permitting researchers to use public funds to reimburse women who donate oocytes directly and solely to stem cell research, not only for the woman's out-of-pocket expenses, but also for the time, burden and discomfort associated with the donation process. The debate about the propriety of such compensation was recently renewed with the publication of a stem cell study in which women were provided with compensation for donating their eggs. This article explores the scientific and ethical rationales that led to New York's decision to allow donor compensation. The multifaceted deliberation process and comprehensive policies may serve as a model for other states and countries considering the issue of oocyte donor compensation.